Influence of carbon nanotube and ionic liquid on properties of natural rubber nanocomposites - A. Krainoi; C. Kummerloewe; Y. Nakaramontri; S. Wisunthorn; N. Vennemann; S. Pichaiyut; S. Kiatkamjornwong; C. Nakason (eXPRESS Polymer Letters)
Some properties of carbon nanotube (CNT) filled natural rubber (NR) composites were improved by adding an ionic liquid (IL), 1-butyl-3-methyl imidazolium bis (trifluoromethylsulphonyl)mide (BMI). In this work, the CNT and IL (CNT-IL) were mixed with NR by latex mixing method. Cure characteristics, thermo-mechanical properties, Payne effect, electrical conductivity and thermal stability were investigated. It was found that IL (BMI) accelerated vulcanization reactions and reduced scorch time. In addition, Fourier Transform Infrared (FTIR) results confirmed the role of IL in NR composites along with the reaction between CNT and NR molecules. The temperature scanning stress relaxation (TSSR) measurement was used to assess thermo-mechanical properties, and a relaxation peak of IL was found due to interactions of cations and anions in IL (BMI). Furthermore, the Payne effect was used to qualitatively analyze the roles of IL and CNT in three-dimensional CNT networks in the NR matrix. It was found that CNT dispersion was finer in the NR/CNT composites with IL. Furthermore, the NR/CNT-IL composite had higher electrical conductivity and lower percolation threshold concentration than the NR/CNT composite.